Genetic manipulation of Methanosarcina spp. - Kohler, Petra R.; Metcalf, William W. (Frontiers in Microbiology, 2012)
The discovery of the third domain of life, the Archaea, is one of the most exciting findings of the last century. These remarkable prokaryotes are well known for their adaptations to extreme environments; however, Archaea have also conquered moderate environments. Many of the archaeal biochemical processes, such as methane production, are unique in nature and therefore of great scientific interest. Although formerly restricted to biochemical and physiological studies, sophisticated systems for genetic manipulation have been developed during the last two decades for methanogenic archaea, halophilic archaea and thermophilic, sulfur-metabolizing archaea. The availability of these tools has allowed for more complete studies of archaeal physiology and metabolism and most importantly provides the basis for the investigation of gene expression, regulation and function. In this review we provide an overview of methods for genetic manipulation of Methanosarcina spp., a group of methanogenic archaea that are key players in the global carbon cycle and which can be found in a variety of anaerobic environments.